Private rescue echo beacon with fsk radiomodule - Moshenskyi, Andrew (Science-based technologies, 2020)
Rescue personnel work in high-risk environments. As a result of injuries, the problem of evacuating the lifeguard from the facility may arise. GPS navigation is not available in restricted areas, for example, in rooms, basements. Rational use of radio responders for direction finding of the object. A radio direct finding complex is not always convenient and can be quickly deployed, for example, in a basement in case of fire. It is more convenient to use the blind bearing method with existing VHF radio stations. Professional radio stations usually do not have an indicator of signal strength, and have limited controls such as volume, channel selection, and PTT. It is proposed to use a carrier transponder at a given frequency based on SI44XX with stepwise adjustable power and synchronously changing audio filling tone in FSK or GFSK mode. Transceivers SI4432, SI4463, CC1101 can be used for this reason. RF power 100-10 mW is enough. All of them can work in FSK GFSK and ASK modes. Widest frequency range have SI4463 and it cover main bands 136-174 MHz and 400-470(512) MHz. The radio module is controlled via the SPI bus; to generate a tone, one of the GPIOs is configured as a binary data input in FSK mode. To implement the response, the module monitors the change of the RSSI and, if it available, switches to the transmission mode. To control the radio module, a simple 8-bit controller with 8 (6) pins and SPI support is enough. A power of 100 mW is more than enough, even with a very shortened helical or other surrogate antenna. Search range of hundreds of metrs is allowed. The number of RF power levels can be 3-4. It can be incree to 7 with an external attenuator on SPDT keys. The power change step is 6-10 dB. The tones are rising, clearly audible in the range of 400-2000 Hz. This system, after the staff training can be useful in the search for the victim in conditions of zero visibility with an accuracy of less than a meter to a few meters in the premises.